A national way to international justice? International Courts vs. national proceedings - Vignola , Marta (Nómadas. Critical Journal of Social and Juridical Sciences, 2009)
This article examines the co-existence of national and international proceeding in the world of law, taking the cases of the Argentina dictatorial militaristic regime of the 70s against Italian citizens as the startpoint and going through other current similar cases.